Hydrodynamics of topological defects in nematic liquid crystals. - Tóth, G; Denniston, C; Yeomans, J (2002)
We show that backflow, the coupling between the order parameter and the velocity fields, has a significant effect on the motion of defects in nematic liquid crystals. In particular, the defect speed can depend strongly on the topological strength in two dimensions and on the sense of rotation of the director about the core in three dimensions.